The Effect of Growth and Root Nodules of Mucuna Bracteata on Various Planting Media Compositions - Samiarjo, Roso; Rochmiyati, Sri Manu; Noviana, Githa (Journal of Agriculture, 2025)
This study aims to determine the effect of growth and root nodules of Mucuna bracteata plants on various planting media compositions. This research was conducted at the Kebun Pendidikan dan Penelitian (KP2) INSTIPER, Maguwoharjo, Depok District, Sleman Regency, from December 2022 to April 2023. This research method is an experimental study arranged in a Completely Randomized Design (CRD). The research treatment consists of 12 treatments consisting of sand+clay+manure, sand+clay+green manure, sand+clay+bioslurry, sand+manure, sand+green manure, sand+bioslurry, clay+manure, clay+green manure, clay+bioslurry, sand, and clay. Each media mixture uses the same volume ratio. The research data were analyzed using ANOVA (Analysis of Variance) at a significance level of 5%, and the real effect was further tested using DMRT at a level of 5%. The results of the study showed that the composition of sand with manure gave the highest fresh root weight results of Mucuna bracteata, namely 8.59 grams, compared with other compositions, such as clay soil, which gave the lowest root weight results, namely 2.07 grams. The sand and bioslurry mixture produced the highest number of root nodules, root nodule weight, and number of effective root nodules in Mucuna bracteata, with figures of 28.40 nodules, 1.05 grams, and 14.80 nodules, respectively. The sand and bioslurry mixture results showed significant differences from those of other planting media mixtures.